CHE685: Fuel and Energy Technology / College of Engineering - UiTM, College of Engineering (2023)
This course is a combination of two areas of studies namely fuel technology and energy technology. The fuel technology covers topics required in the conventional sources of energy such as types of fuel and combustion calculations involved in the energy production. The energy technology covers the present form of the world energy consumption and production. The current trends in the global energy needs and its sustainability are particularly highlighted and emphasized also include renewable sources of energy.